ANALISIS POLA KEMITRAAN PEMBENIHAN MENTIMUN (Cucumis sativus L.) DALAM MENINGKATKAN PENDAPATAN USAHATANI - Nurani, Maria Puri; Perwita Rahmanti Ignatia, Sari; Chrismonika, Maria (BiSTeK Pertanian, 2024)
Barriers to horticulture in several developing countries, including Indonesia, include low farmer income, limited farmer knowledge, limited farmer land ownership, and weak farmer supply situations. This results in reduced profits for farmers. One way to overcome these obstacles that can be done by the Rukun Tani farmer group is to establish a partnership with PT Agri Makmur Pertiwi. This study aims to analyze the partnership pattern in cucumber hatcheries and its impact on increasing farm income. This research used descriptive qualitative and quantitative methods with a case study approach on 20 respondents who established partnerships with hatchery companies. Data were collected through questionnaires, in-depth interviews, field observations, and documentation. Data were tested using the t-test. The results show that the partnership pattern applied is a core-plasma partnership, where the core company provides production facilities, provides guidance, transportation costs, and market guarantees. The farmer group acts as a plasma that provides land, labor, agricultural tools, fertilizers, and manages cucumber farming according to the standards set by the core company. The results of the difference test show that there are differences in income before and after partnering. Income before partnering was IDR 18,053,507.5 and income after partnering was IDR 35,622,807.5.